Growth conditions and environmental factors impact aerosolization but not virulence of Francisella tularensis infection in mice - Faith, Seth; Smith, Le'Kneitah; Swatland, Angela; Reed, Douglas S. (Frontiers in Cellular and Infection Microbiology, 2012)
In refining methodology to develop a mouse model for inhalation of Francisella tularensis, it was noted that both relative humidity and growth media impacted the aerosol concentration of the live vaccine strain (LVS) of F. tularensis. A relative humidity of less than 55% had a negative impact on the spray factor, the ratio between the concentration of LVS in the aerosol and the nebulizer. The spray factor was significantly higher for LVS grown in brain heart infusion (BHI) broth than LVS grown in Mueller-Hinton broth (MHb) or Chamberlain’s Chemically Defined Medium (CCDM). The variability between aerosol exposures was also considerably less with BHI. LVS grown in BHI survived desiccation far longer than MHb-grown or CCDM-grown LVS ( 70% at 20 minutes for BHI compared to <50% for MHb and CCDM). Removal of the capsule by hypertonic treatment impacted the spray factor for CCDM-grown LVS or MHb-grown LVS but not BHI-grown LVS, suggesting the choice of culture media altered the adherence of the capsule to the cell membrane. The choice of growth media did not impact the LD50 of LVS but the LD99 of BHI-grown LVS was 1 log lower than that for MHb-grown LVS or CCDM-grown LVS. Splenomegaly was prominent in mice that succumbed to MHb- and BHI-grown LVS but not CCDM-grown LVS. Environmental factors and growth conditions should be evaluated when developing new animal models for aerosol infection, particularly for vegetative bacterial pathogens.